2017
DOI: 10.1080/10942912.2017.1381702
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of gelatin extracted from croaker fish (Johnius sp) skin waste

Abstract: In the present study, the gelatin from fresh croaker fish (Johnius sp) skin was obtained by rapid extraction and its properties were assessed. The gelling and melting temperature of croaker skin gelatin was 17.4 and 23.8°C as revealed by dynamic visco-elastic analysis using Controlled Stress Rheometer. Croaker skin gelatin (CSG) had the bloom value of 193.4 g. Scanning electron microscopic analysis of freeze dried gelatin showed the presence of voids surrounded by a loose network imitating a sponge or coral li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 34 publications
0
23
2
Order By: Relevance
“…As shown in Table 1, the gelling and melting temperatures of G45, G55, and G65 were 19.3-23.4 • C and 28.9-32.3 • C, respectively, and there was no marked difference among all bullfrog skin gelatins and PG (p > 0.05). The gelling and melting temperatures in this study were higher than those of gelatins from the skins of camel (15.2-11.1 and 18.4-21.6 • C, respectively) [9], croaker fish (17.4 • C and 23.8 • C, respectively) [33] and similar with goat skin gelatin (21.2-25.2 • C and 30.7-34.1 • C, respectively) [20]. The difference in the gelling and melting properties of bullfrog gelatin compared with other gelatins can be attributed to the difference in extraction conditions, amino acid compositions, and protein chain length [29].…”
Section: Temperature Sweepcontrasting
confidence: 55%
“…As shown in Table 1, the gelling and melting temperatures of G45, G55, and G65 were 19.3-23.4 • C and 28.9-32.3 • C, respectively, and there was no marked difference among all bullfrog skin gelatins and PG (p > 0.05). The gelling and melting temperatures in this study were higher than those of gelatins from the skins of camel (15.2-11.1 and 18.4-21.6 • C, respectively) [9], croaker fish (17.4 • C and 23.8 • C, respectively) [33] and similar with goat skin gelatin (21.2-25.2 • C and 30.7-34.1 • C, respectively) [20]. The difference in the gelling and melting properties of bullfrog gelatin compared with other gelatins can be attributed to the difference in extraction conditions, amino acid compositions, and protein chain length [29].…”
Section: Temperature Sweepcontrasting
confidence: 55%
“…The highest values of hardness were found in PG, TG‐FG2, P‐FG1, and P‐FG2, while P‐FG3 gave lowest ( p < .05). Higher hardness values indicate the maximum force required to compress the food between molar teeth (Kumar et al, ). Adhesiveness is defined as the work necessary to overcome the attractive forces between the product and a specific surface.…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin, being low in calories, is widely used in food, photographic, cosmetic, biomedical, pharmaceutical, and neutraceutical industries (Al‐Kahtani et al, ; Kumar, Chandra, Elavarasan, & Shamasundar, ; Sha et al, ; Yu et al, ). It has been reported that the global demand for gelatin is expected to reach 450.7 kt in 2018 (Huang et al, ), with around 98.5% is extracted from mammalian sources including pig skins, bovine hides, and beef bones, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of amino acids was of particular importance regarding the characteristics of collagen and gelatin, such as gel strength and melting point. The high rigidity of R-groups in amino acids, as well as the high contents of hydrophobic amino acids, might significantly improve the stability of triple helix structures in collagen (Kumar et al, 2017).…”
Section: Amino Acid Analysismentioning
confidence: 99%